Зина Портнова: истории о пионерах-героях / Дмитрий Пронин - Пронин Дмитрий (Вы и ваш ребенок, 2017)
Экземпляры: ф.9 (2022) / Инвентарный номер: 58327 / Цена: / Сис.шифр: 63.3(2)622.5 / Авт.знак: П 78 / ГРНТИ: 14.27 / ББК: 74.27